Estudo das mutações germinativas nos genes de reparo e Epcam em pacientes com suspeita Síndrome de Lynch - Pimenta, Celia Aparecida Marques [UNIFESP] (2018)
Background: Lynch syndrome (SL) is the most common inherited colorectal cancer (CRC) syndrome, representing 2 to 4% of all cases of CRC, because presenting few polyps is also known as HNPCC (nonpolypoid hereditary colorectal cancer). Most subjects with SL have at least one pathogenic mutation of the MMR (mismatch repair) genes MLH1, MSH2, MSH6 or PMS2. Objectives: Evaluate patients with CRC and gastric cancer (GC) with suspicion of SL by immunohistochemistry and sequencing of DNA repair genes, and EPCAM. Patients and methods: We analyzed 116 medical records of patients with CRC and GC related to SL with at least one of the Bethesda criteria, after an interview with a patient and consultation with a geneticist. An immunohistochemical test and a new generation sequencing (NGS) of repair genes was performed to investigate the expression of the repair proteins, EPCAM and BRAF. Results: Among the 116 patients, 95 were considered eligible. The mean age at diagnosis of CRC or CG in women was 50.7 years and in men 54.03. Regarding the tumor location, 40% presented tumor in the right colon, 60% had a moderately differentiated histological grade. Immunohistochemistry was performed to study the immunoexpression of the repair proteins in 95 samples of tumors tissue and 75.6% had absence of expression in at least 1 of the proteins. Among tumors with some mutations, 74% of the patients were younger than 50 years and 47% of the CRC were on left colon. NGS was performed on 95 blood samples. The MLH1 gene had 13% of pathogenic mutations, MSH2 7%, MSH6 5%, and EPCAM 1%. The number of patients affected by some mutation corresponded to 30% (29/95). Conclusion: The MLH1 gene mutation was the most frequent. The percentage of pathogenic mutations of the EPCAM gene was very rare. Approximately 50% of the patients with absence of expression of the repair genes presented pathogenic mutation at sequencing. This difference reinforces the importance of the sequencing study among patients with altered expression of repair proteins.